Rare upper gastrointestinal hemorrhage of cetuximab: A case report. Issue 51 (December 2017) - Duan, Shi-Jie; Gao, Zi-Ming; Wang, Peng-Liang; Gong, Bao-Cheng; Huang, Han-Wei; Luo, Lei; Wang, Xin; Xing, Ya-Nan; Xu, Hui-Mian; Liu, Fu-Nan
Abstract: Rationale: cetuximab, an epidermal growth factor receptor inhibitor, is a targeted therapeutic regimen of colorectal cancers. Several common adverse effects have been found, such as cutaneous or gastrointestinal toxicity. However, according to the articles had been published, upper gastrointestinal bleeding (UGIB) is considered to be rare and its mechanism remains unclear. Patient concerns: In this report, we presented a 42-year-old male patient with advanced recto-sigmoid cancer. After palliative operation, the patient suffered from complete upper gastrointestinal (GI) obstruction, which was induced by extensive abdominal metastasis of the tumor. Considering his poor condition, we chose the targeted drug, cetuximab, as his further treatment. But after the application of cetuximab, the UGIB immediately happened twice in this patient. Diagnosis: UGIB, as a rare complication of cetuximab, occured to the patient. Interventions: We stopped the bleeding with thrombin, hemocoagulase and somatostatin and suspended the subsequent treatment plan of cetuximab. At the same time, anti-shock treatment was given immediately. Outcomes: He was died of respiratory and circulatory failure caused by UGIB and advanced tumor eventually. Lessons: UGIB should be considered as a rare but severe complication of cetuximab. When cetuximab is applied for patients with advanced colon tumors, more cautions should be required if the patients are accompanied by upper gastrointestinal obstruction. In addition, for those patients who suffered from UGIB recently, cetuximab should be prohibited if the Rockall score ranged > 5 points.